Carbon encapsulated NiCo2S4 nanoparticles with enhanced surface mediated charge storage for superior ultracapacitor electrodes - Chaturvedi, Vikash; Pawar, Meenakshi; Thripuranthaka, M.; Shivade, Rajkiran; Shelke, Manjusha V. V. (Chemistry-An Asian Journal, 2023)
Three different compositions of NiCo2S4 (NCS) materials were prepared using three solvents, named NCS HTDI (hydrothermal in DI water), NCS STEG (solvothermal in ethylene glycol), and a novel carbon-encapsulated NCS STFA (solvothermal in formamide). The structural and morphological properties of the prepared NCS HTDI, NCS STEG, and NCS HTDI materials were analyzed using various physical characterization techniques. As prepared, NCS materials were tested as an electrode for supercapacitor (SC) application using a 3-electrode system in a basic electrolyte (3 M KOH). NCS HTDI exhibits a specific capacitance of 2536 F g(-1), NCS STEG shows 1355 F g(-1), and NCS STFA shows 1178 F g(-1) at an input current density of 1 A g(-1). The SBN-PSC material is utilized as a counter electrode in the NCS STFA || SBN-PSC-based asymmetric SC device. The device exhibits exceptionally superior electrochemical performance with a specific capacitance of 172 F g(-1) at 10 A g(-1) input current density and 97% capacity retention after 5000 cycles in a voltage window of 1.6 V. The results confirm the superiority of NCS STFA||SBN-PSC deviceas an excellent high-energy and high-power SC.
Keywords: Asymmetric supercapacitor device; NiCo2S4; pseudocapacitor; Surface charge storage